2022
DOI: 10.3390/v14112544
|View full text |Cite
|
Sign up to set email alerts
|

Detection Analysis and Study of Genomic Region Variability of JCPyV, BKPyV, MCPyV, HPyV6, HPyV7 and QPyV in the Urine and Plasma of HIV-1-Infected Patients

Abstract: Since it was clearly established that HIV/AIDS predisposes to the infection, persistence or reactivation of latent viruses, the prevalence of human polyomaviruses (HPyVs) among HIV-1-infected patients and a possible correlation between HPyVs and HIV sero-status were investigated. PCR was performed to detect and quantify JCPyV, BKPyV, MCPyV, HPyV6, HPyV7 and QPyV DNA in the urine and plasma samples of 103 HIV-1-infected patients. Subsequently, NCCR, VP1 and MCPyV LT sequences were examined. In addition, for MCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…3 Despite exhibiting similar symptomatology, two distinct MCC etiologies have been identified. 4,5 Nearly 80% of MCC cases are caused by a DNA tumor virus named Merkel cell polyomavirus (MCPyV), 6 that is, MCPyV-positive MCC (MCCP). 7 The remaining MCCs result as MCPyV-negative (MCCN).…”
Section: Introductionmentioning
confidence: 99%
“…3 Despite exhibiting similar symptomatology, two distinct MCC etiologies have been identified. 4,5 Nearly 80% of MCC cases are caused by a DNA tumor virus named Merkel cell polyomavirus (MCPyV), 6 that is, MCPyV-positive MCC (MCCP). 7 The remaining MCCs result as MCPyV-negative (MCCN).…”
Section: Introductionmentioning
confidence: 99%
“…Although JCPyV infects the kidney, the brain is typically the site of pathology, so the virus must travel between the organs. In patients with PML, the JCPyV in the brain is genotypically different from the virus in the kidney [ 21 , 27 , 125 , 126 , 127 , 128 , 129 , 130 ]. Polyomaviruses residing in the kidney typically exhibit the archetype strain.…”
Section: How Does Polyomavirus Travel From the Periphery To The Brain?mentioning
confidence: 99%
“…Viral shedding increases and results in lytic infection. Patient studies have shown that the NCCR undergoes rearrangements in two human immunodeficiency virus (HIV)-positive patients with PML [ 127 , 134 , 135 ]. One study found that HIV-negative MS patients with PML did not have complex rearrangements, suggesting that either T helper cell depletion or HIV itself may play a role in NCCR rearrangement [ 29 ].…”
Section: How Does Polyomavirus Travel From the Periphery To The Brain?mentioning
confidence: 99%